(untitled) (Zaporizhzhia Historical Review, 2021)
In the research questions of becoming and development of city public bank in a Aleksandrovsk provinces Ekaterinoslavskoj are considered. The author investigated history of occurrence of the first bank establishment of city. On the basis of the revealed archival documents connected with activity Aleksandrovsk of city public bank the author opens unknown pages of history of development of a banking in Zaporozhye. Clause is calculated on historians, regional specialists and all those to whom the history of city of Zaporozhye is interesting